Pengembangan Sistem Informasi Ujian Sekolah Berbasis Intranet DI SMK Basyariyah Madiun - sujarwo sujarwo (Universitas Trunojoyo Madura, 2015)
AbstractThis study develops school management are now many who utilize information systems, such as the Academic Information Systems, Information Systems Officer and others. But the system is still manual examination conducted that the teachers should make printed matter and must be propagated so it takes a long time as well as substantial funds for the preparation of the manuscript matter and answer sheet. Students also have to write it manually using pens to answer such questions. The efficiency and effectiveness of the exam committee less can optimally process the student assessment test results. By implementing a needs analysis (requirement analysis) to determine the needs of the system, then the author can specify a matter of necessity in the course of this intarnet based school exams, by making a new form of learning systems by implementing an intranet-based school examination system, providing convenience to each teacher in the field of study melaksankan school exams to students, to look for effective learning solution is to create an intranet-based school examination system, to develop skills in information technology-based learning. Exam Application Design School The school will be applied in the intranet, where these applications can be accessed by all computers clien in one room, so that examinees can access the questions from the server to the model question multiple choice / multiple choice is random and student test carried out in komputer.sehingga lab can provide efficiency in various aspects, namely the efficiency of time and cost efficiency. Design of information systems intranet-based school exam this is by using the PHP programming language and MySQL database MySQL used a database that has a very high process capability and save memory, it is very supportive of the school information system web-based exam.Keywords: Information Systems; php; MySql.